RAF inhibitors promote RAS-RAF interaction by allosterically disrupting RAF autoinhibition - Ting Jin; Hugo Lavoie; Malha Sahmi; Maud David; Christine Hilt; Amy Hammell; Marc Therrien (Nature Communications, 2017)
RAF family kinases transmit signals from activated RAS at the plasma membrane to downstream kinases to control cell proliferation, differentiation and survival. Here the authors shed light on the molecular mechanisms whereby small molecule RAF inhibitors induce RAS-RAF association and paradoxical RAF activation.